Copolyester nanocomposites based on carbon nanotubes: reinforcement effect of carbon nanotubes on viscoelastic and dielectric properties of nanocomposites - Kalgaonkar, Rajendra A.; Jog, Jyoti Prakash (Polymer International, 2008)
Nanocomposites based on an amorphous copolyester, poly(ethylene glycol-co-cyclohexane-1,4-dimethanol terephthalate) and carbon nanotubes were fabricated using a simple melt processing technique. The reinforcement effect of carbon nanotubes in the copolyester was investigated experimentally using different approaches based on dynamic mechanical analysis, theology and dielectric analysis. The nanocomposites show a mechanical reinforcement effect with significant increase in the stiffness especially in the rubbery regime with increasing nanotube content. An increase in T-g and a decrease in damping are seen, which are derived from the presence of a percolating superstructure of the filler. Rheological experiments show an increase in storage modulus up to four orders of magnitude. Viscolelastic characterization shows that the percolation threshold is at 3 wt% of nanotubes. Dielectric relaxation spectroscopy confirms the presence of this percolating structure. We conclude that the responses of both rheological and electrical properties are different, although both are related to the formation of a percolating network superstructure of the filler. (c) 2007 Society of Chemical Industry.
Keywords: Carbon nanotubes; dielectric analysis; nanocomposites.; reinforcement; viscoelastic properties